2003
DOI: 10.1023/b:thro.0000011376.12309.af
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Induced Sensitivity to Warfarin: A Review of the Literature

Abstract: Warfarin is a widely prescribed anticoagulant used for prophylaxis and treatment of venous and arterial thrombosis. Although warfarin is considered very efficacious, it has substantial risks associated with its use, specifically the risk of hemorrhage. Genetic variants associated with the metabolism of (S)-warfarin by cytochrome P450 2C9 may have specific implications on untoward effects. Twelve CYP2C9 allelic variants have been identified, of which CYP2C9*3 and CYP2C9*2 are the most clinically important. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
13
0
3
Order By: Relevance
“…Consequently, the effect of CYP2C9 polymorphism on phenprocoumon metabolism and anticoagulant response is moderate. Surprisingly, in a study performed in 201 patients, mostly of Swedish origin, an association between the CYP2C9*2 polymorphism (rs1799853) and decrease in warfarin dose was found to be not significant by univariate analysis (Palkimas et al, 2003;. The hypomorphic allele CYP2C9*3 (rs1057910), which abolishes CYP2C9-catalyzed metabolism of S-warfarin, was strongly associated with warfarin dose, in accordance with previous findings (Margaglione et al, 2000).…”
Section: Genotype As a Warfarin-related Risk Factorsupporting
confidence: 77%
See 2 more Smart Citations
“…Consequently, the effect of CYP2C9 polymorphism on phenprocoumon metabolism and anticoagulant response is moderate. Surprisingly, in a study performed in 201 patients, mostly of Swedish origin, an association between the CYP2C9*2 polymorphism (rs1799853) and decrease in warfarin dose was found to be not significant by univariate analysis (Palkimas et al, 2003;. The hypomorphic allele CYP2C9*3 (rs1057910), which abolishes CYP2C9-catalyzed metabolism of S-warfarin, was strongly associated with warfarin dose, in accordance with previous findings (Margaglione et al, 2000).…”
Section: Genotype As a Warfarin-related Risk Factorsupporting
confidence: 77%
“…This finding was confirmed multiple times in different populations (for recent works, see Herman et al, 2005;Voora et al, 2005;Loebstein et al, 2006;Obayashi et al, 2006;Tham et al, 2006); several review articles summarized these observations (Daly and King, 2003;Palkimas et al, 2003;Wadelius and Pirmohamed, 2006). Although CYP2C9 is the major catalyst responsible for biotransformation of warfarin and a closely related acenocoumarol, CYP2C9-catalyzed metabolism of another warfarin analog, phenprocoumon, is less important.…”
Section: Genotype As a Warfarin-related Risk Factormentioning
confidence: 63%
See 1 more Smart Citation
“…The CYP2C9.2 allozyme is reported to display approximately 12% of the native CYP2C9.1 allozyme activity. 3,4,17 All other results on this sample were within normal operating parameters of the assay and indicated that this sample was homozygous for the CYP2C9*1 nucleotide sequence at all other positions tested. The objective of this study was to determine the basis for this ''no call'' result of the CYP2C9*2 allele-specific primers.…”
Section: Introductionmentioning
confidence: 90%
“…1,2 Several alleles of CYP2C9 have been identified that encode proteins with little or no metabolic activity. [1][2][3] Diagnostic assays for research and clinical genotyping are being developed and used with particular regard to the proper dosing of patients with the anticoagulant warfarin. 1 Our laboratory routinely uses a multiplex genotyping assay that is based on the principle of allelespecific primer extension (ASPE).…”
Section: Introductionmentioning
confidence: 99%